Reviewer acknowledgements for Journal of Bahasa & Sastra, Vol.15, No.2, October 2015 - Sukyadi, Didi (Universitas Pendidikan Indonesia, 2015)
Reviewer acknowledgements for Journal of Bahasa Sastra, Vol.15, No.2, October 2015